2017
DOI: 10.1159/000455916
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of S-777469, a Cannabinoid Type 2 Receptor Agonist, on Skin Inflammation in Mice

Abstract: We investigated the effects of S-777469 (1-[[6-Ethyl-1-[4-fluorobenzyl]-5-methyl-2-oxo-1, 2-dihydropyridine-3-carbonyl]amino]-cyclohexanecarboxylic acid), a novel cannabinoid type 2 receptor (CB2) agonist, on 1-fluoro-2,4-dinitrobenzene (DNFB)-induced ear inflammation and mite antigen-induced dermatitis in mice. The oral administration of S-777469 significantly suppressed DNFB-induced ear swelling in a dose-dependent manner. In addition, S-777469 significantly alleviated mite antigen-induced atopic dermatitis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…As seen in macroscopic analysis, the effect of the COX inhibitor diclofenac was similar to anti-inflammatory effect of CB2 agonist. Haruna et al (34), have showed that the S-777469, (CB2) agonist, reduced the epidermal thickness and the number of mast cells infiltrating skin lesions of DNFB-induced ear swelling in mice. MAGL inhibition in diseased mice increased 2-arachidonoylglycerol levels, leading to a reduction of macroscopic and histological colon alterations in the trinitrobenzene sulfonic acid (TNBS)-induced colitis (31).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in macroscopic analysis, the effect of the COX inhibitor diclofenac was similar to anti-inflammatory effect of CB2 agonist. Haruna et al (34), have showed that the S-777469, (CB2) agonist, reduced the epidermal thickness and the number of mast cells infiltrating skin lesions of DNFB-induced ear swelling in mice. MAGL inhibition in diseased mice increased 2-arachidonoylglycerol levels, leading to a reduction of macroscopic and histological colon alterations in the trinitrobenzene sulfonic acid (TNBS)-induced colitis (31).…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid system is involved in attenuation of the skin allergic response: in mice with experimentally induced skin allergy, genetic ablation of CBR1 and CBR2 resulted in a more severe dermatitis and higher skin levels of PEA compared with wild‐type counterparts . Furthermore, CBR1 inhibited epidermal keratinocyte growth and different CBR2 agonists reduced skin inflammation in several experimental models of allergy . As such, the increased CBR1 and CBR2 expression in feline HD skin, as well as CBR2 immunoreactivity of dermal resident and infiltrating cells might be regarded as a skin response to inflammation, aimed at restoring homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…CBR1 and CBR2 also are overexpressed in the skin of dogs affected with atopic dermatitis . Implications for skin protective action of cannabinoid receptor agonists have been repeatedly suggested, and CB receptors are considered to play a crucial role in epidermal differentiation and recovery of the epidermal permeability barrier . Currently, evidence suggests that agonism at CB and CB‐related receptors may represent a novel treatment approach to common inflammatory/allergic skin diseases …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that CB1 agonists relieve inflammatory symptoms [59] by downregulating mast cell activation [60] and decreasing keratinocyte-derived proinflammatory mediators [61]. In addition, CB2 agonists suppress skin inflammation by inhibiting inflammatory cell migration [62], and GPR55, which is found in mast cells, has anti-inflammatory effects by inhibiting mast cell-mediated release of nerve growth factor and reducing angiogenesis [63]. In our study, the results indicate that HTD generates ECS components such as CB1, CB2, and GPR55.…”
Section: Discussionmentioning
confidence: 99%